Delphi Project on the trends in Implant Dentistry in the COVID‐19 era: Perspectives from Latin America. Issue 4 (15th March 2021) - Alarcón, Marco Antonio; Sanz‐Sánchez, Ignacio; Shibli, Jamil Awad; Treviño Santos, Alejandro; Caram, Santiago; Lanis, Alejandro; Jiménez, Paola; Dueñas, Ricardo; Torres, Ronald; Alvarado, Jacinto; Avendaño, Adrián; Galindo, Roberto; et al.
Abstract: Aim: To establish trends in Implant Dentistry in Latin America in the COVID‐19 pandemic. Material and methods: A steering committee and an advisory group of experts in Implant Dentistry were selected among eighteen countries. An open‐ended questionnaire by Delphi methodology was validated including 64 questions, divided in 7 topics, concerning the various trends in dental implantology. The survey was conducted in two rounds, which provided the participants in the second round with the results of the first. The questionnaires were completed on August 2020, and the online meeting conference was held on September 2020. The final prediction was developed through consensus by a selected group of experts. Results: A total of 197 experts from Latin America answered the first and second questionnaire. In the first round, the established threshold for consensus (65%) was achieved in 30 questions (46.87%). In the second round, performed on average 45 days later, this level was achieved in 47 questions (73.43%). Consensus was completely reached on the item "Diagnostic" (100%), the field with the lowest consensus was "Demand for treatment with dental implants" (37.5%). Conclusions: The present study in Latin America has provided relevant and useful information on the predictions in the education and practice of Implant Dentistry in the COVID‐19 era. The consensus points toward a great confidence of clinicians in the biosecurity protocols used to minimize the risk of SARS‐CoV‐2 transmission. It is foreseen as an important change in education, with introduction of virtual reality and other simulation technologies in implant training.